2014
DOI: 10.1159/000369666
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Suicidal Erythrocyte Death by Artesunate

Abstract: Background: The artemisinin derivative artesunate is effective in the treatment of severe malaria and is considered for the treatment of malignancy. Artesunate triggers tumor cell apoptosis, an effect at least in part mediated by mitochondria. Even though lacking mitochondria, erythrocytes may similarly enter suicidal death or eryptosis, which is characterized by cell shrinkage and breakdown of the phospholipid asymmetry of the cell membrane with phosphatidylserine translocation to the erythrocyte surface. Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 82 publications
(28 citation statements)
references
References 132 publications
(152 reference statements)
0
28
0
Order By: Relevance
“…Studies have reported immunosuppressive or inhibition of erythropoiesis (Finaurini et al, 2010;Wang et al, 2007;Yang et al, 2005), and other adverse effects of artemisinin derivatives both in the presence or absence of malaria parasites including hemolytic effects (Alzoubi et al, 2014;Anaba et al, 2012;Garba and Ubom, 2005;Gu et al, 1986;Kurth et al, 2016;Lee et al, 2015;Orjih, 1996;Zhou et al, 2005), many of which appear to be non-severe. The mechanism for inducing delayed post-artemisinin hemolysis when administered as monotherapy or co-administered with a partner drug such as amodiaquine remains to be understood.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported immunosuppressive or inhibition of erythropoiesis (Finaurini et al, 2010;Wang et al, 2007;Yang et al, 2005), and other adverse effects of artemisinin derivatives both in the presence or absence of malaria parasites including hemolytic effects (Alzoubi et al, 2014;Anaba et al, 2012;Garba and Ubom, 2005;Gu et al, 1986;Kurth et al, 2016;Lee et al, 2015;Orjih, 1996;Zhou et al, 2005), many of which appear to be non-severe. The mechanism for inducing delayed post-artemisinin hemolysis when administered as monotherapy or co-administered with a partner drug such as amodiaquine remains to be understood.…”
Section: Discussionmentioning
confidence: 99%
“…Signaling of eryptosis includes increase of cytosolic Ca 2+ activity ([Ca 2+ ]) [13], ceramide [14], oxidative stress [13], energy depletion [13], heterotrimeric G-protein subunit Gαi2 [15], caspases [13, 16, 17], casein kinase 1α [13], Janus-activated kinase JAK3 [13], protein kinase C [13], and p38 kinase [13]. Eryptosis is inhibited by AMP activated kinase AMPK [13], cGMP-dependent protein kinase [13], PAK2 kinase [13], mitogen- and stress-activated kinase MSK1/2 [18], as well as sorafenib/sunitinib sensitive kinases [13]. Enhanced eryptosis contributes to anemia in a variety of clinical conditions [15, 19-27] and is enhanced following blood storage for transfusion [28].…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced eryptosis contributes to anemia in a variety of clinical conditions [15, 19-27] and is enhanced following blood storage for transfusion [28]. Eryptosis is triggered by many xenobiotics [13, 16, 20, 21, 25, 29-71] including bacterial Lpp [72]. However, the structural requirements for bacterial Lpp-induced eryptosis are ill-defined.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, eryptosis is triggered by activated casein kinase 1α, Janus-activated kinase JAK3, protein kinase C, p38 kinase, and PAK2 kinase [25], as well as by inhibited or lacking AMP activated kinase AMPK, cGMP-dependent protein kinase, sorafenib sensitive kinases and sunitinib sensitive kinases [25]. Stimulators of eryptosis further include diverse xenobiotics [25,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57]. …”
Section: Introductionmentioning
confidence: 99%